Constructing Moral Legitimacy through Empathic and Inferential Strategies in Political Discourse toward a Cognitive–Pragmatic Model of Diplomatic Persuasion - Priadi, Arum; Medi Prasetyo (Forum Akademisi dan Dosen Peneliti (FAST), 2025)
This study investigates President Prabowo Subianto’s 2025 address to the United Nations General Assembly through the integrated framework of Cognitive Pragmatics and Relevance Theory. It explores how persuasion in diplomatic discourse operates as a distributed cognitive process rather than a mere rhetorical performance. The analysis combines qualitative pragmatic interpretation with corpus-assisted evidence using AntConc to identify patterns of attention, inference, and empathy in the speech. Findings reveal that ostensive cues function as attentional scaffolds directing the audience’s cognitive focus, while inferential mechanisms co-construct moral legitimacy through shared reasoning. Empathy, manifested lexically and prosodically, emerges as a relevance amplifier that fuses affective alignment with inferential cooperation. Quantitative corpus results particularly the high frequency of moral and relational lexemes such as peace, justice, humanity, and together confirm the centrality of moral cognition in persuasive framing. The study extends Relevance Theory by proposing empathy as an epistemic variable mediating the affective–inferential continuum of meaning. It concludes that political persuasion, especially within Global South diplomacy, functions as a cognitive negotiation of shared moral relevance, where understanding and empathy become sources of communicative authority. This research thus contributes to the theoretical expansion of Relevance Theory, the methodological integration of corpus pragmatics, and the empirical understanding of moral cognition in global political communication.